Association between sacubitril/valsartan initiation and real‐world health status trajectories over 18 months in heart failure with reduced ejection fraction. (1st May 2021) - Thomas, Merrill; Khariton, Yevgeniy; Fonarow, Gregg C.; Arnold, Suzanne V.; Hill, Larry; Nassif, Michael E.; Chan, Paul S.; Butler, Javed; Thomas, Laine; DeVore, Adam D.; Hernandez, Adrian F.; Albert, Nancy M.; et al.
Abstract: Aims: Improving the health status (symptoms, function, and quality of life) of patients with heart failure with reduced ejection fraction (HFrEF) is a primary treatment goal. Angiotensin receptor neprilysin inhibitors (ARNI) improve short‐term health status in clinical practice, but the sustainability of these improvements is unknown. Methods and results: In CHAMP‐HF, a multicentre observational study of outpatients with HFrEF, patients initiated on ARNI were propensity score matched 1:2 to patients not using ARNI with Cox regression modelling time to ARNI initiation, adjusted for sociodemographic and clinical variables, medical history, medications, and baseline Kansas City Cardiomyopathy Questionnaire (KCCQ) scores. Repeated measures models for the overall KCCQ score and each domain compared the health status trajectories of patients initiated on ARNI vs. not. Among 3930 participants, 746 (19.0%) began ARNI, of whom 576 were matched to 1152 non‐ARNI patients. Prior to matching, participants initiated on ARNI were younger, non‐Hispanic, had lower EFs, more commonly had a history of ventricular arrhythmia, were less likely to be taking an ACEI/ARB, and more likely to be treated with beta‐blockers and mineralocorticoid receptor antagonists. There were no differences after matching. In the matched cohort, participants initiated on ARNI experienced improved health status by 3 months that persisted through 12 months [KCCQ Overall Summary Score (OSS) = 73.4 vs. 70.8; P < 0.001], with the largest benefit observed in the KCCQ Quality of Life domain (68.7 vs. 64.7; P < 0.001). Similar health status benefits were noted through 18 months (KCCQ‐OSS = 73.9 vs. 71.3; P < 0.001). A responder analysis showed that 12 patients would need to be initiated on ARNI for one to experience at least a large improvement (≥10 points) in health status benefit at 12 months. Conclusions: In outpatient practice, ARNI therapy was associated with improved health status by 3 months and continued to 18 months after initiating therapy.